Avaliação de polimorfismo no gene BRCA1 em cadelas com tumores mamários - Ferreira, Camila Calvi Menegassi (2018)
Breast tumors (TM) are highly incidental in whole adult females and have a multifactorial pattern. The BRCA1 gene is a tumor suppressor gene because mutations in it cause defects in the repair of DNA damage and genetic instability that favors tumorigenesis. It is directly related to the risk of developing familial human breast cancer. There are few veterinary studies that associate the development of canine TM with single nucleotide polymorphisms (SNPs) found in BRCA1. Thirty-six malignant TM samples were submitted to DNA extraction, PCR and genetic sequencing, and six samples that formed a control group. Ten different histological types of tumors were found. Complex carcinoma was the tumor with the highest incidence with 33.33%. Three different SNP sites were identified in five samples. Two at 3761C> T, and one at 4006G> A that caused amino acid change, and classified by the PolyPhen Software as harmful. And two SNPs in 3619A> G, which also caused amino acid substitution, but was considered by the Software as benign. In conclusion, SNPs in the BRCA1 gene can cause loss of protein structure, causing loss of function, thus favoring the process of carcinogenesis.